Faktor Internal Dan Eksternal Yang Berpengaruh Terhadap Kinerja Perusahaan - Heti Herawati; Muhammad Farhan Surya (Jurnal Ilmiah Manajemen Kesatuan, 2023)
This study aimed to determine the effect of current ratio, DER, company size, sales growth, inflation, and interest rate on company performance. The sample in this study were 160 property and real estate sub-sector service companies that listed on Indonesia Stock Exchange in 2015 – 2019 and had complete annual and financial reports. This study used purposive sampling as the sampling technique. The data used in this study were secondary data from the companies’ annual and financial reports. The results of this study showed a significant effect between current ratio, DER, total assets, GS, inflation, and interest rates with company performance (Fscore Ftable). The contribution was 33,6% (R2 = 0,036). The results of t test also showed that DEF, total assets, inflation, and interest rates significantly affect company performance (p < 0,05) but there was no significant effect between current ratio and GS with company performance (p < 0,05). Keywords: Current ratio, DER, Total assets, GS, inflation, interest rate, company performance, ROE